A report on the impacts of cyclone Yaas over a fish landing centre vulnerable to cyclonic storms and natural hazards – Talsari, Northern Odisha. Issue 9 (2nd September 2021) - Kundu, Sudip Kumar; Santhanam, Harini
ABSTRACT: The present work reports the actual ground conditions prevalent at a fish landing centre in Northern Odisha, namely, Talsari in the aftermath of the cyclone "Yaas", which made a landfall on May 26th, 2021. Local surveys showed the extensive damages to the fishing and tourism infrastructures, denoting huge setbacks to the pursuance of sustainable fishing practices. The combined stress of the lockdown due to COVID-19 pandemic as well as the successive damages to livelihoods due to the cyclones Amphan and Yaas in 2020 and 2021 respectively, has increased the risk and vulnerability of Balasore to natural hazards by multiple folds. The same requires multi-agency intervention and detailed analyses of local socio-technical factors to avoid futuristic losses.